Perceptions Of Madrassa Students And Teachers Towards English Language Learning - Syed Sajjad Ali (University of Chitral Journal of Linguistics and Literature, 2020)
The purpose of this descriptive research study is to find out the perceptions of students and teachers about the problems and challenges in learning and teaching of English language in Madrassas located in urban area of District Mardan. The main objectives of the study are to assess the attitude of both the students and teachers towards English language; to find out the required facilities for the teaching and learning of English and to put forward the recommendations of the students and teachers for the eradication of the problems and challenges to English language learning and teaching in Madrassas. The population of the research study consist of all Madrassas and all male students and teachers in Urban Madrassas in District Mardan. The researchers use convenient sample for the selection of Madrassas. Selection of students is based on thirty percent proportionate sample; while teachers are selected on the basis of hundred percent proportionate samples accordingly. Two separate questionnaires are the instrument for data collection. The questionnaires comprised on both closed and open ended items. The collected data were analyzed using percentage and thematic analysis. Findings of the study revealed that there are no proper facilities for the teaching of English language. The results of this research study may be helpful for the policy makers to emphasize more on the importance of English language learning in Madrassas across Pakistan and Khyber Pakhtunkhwa in particular.